Knowledge management positioning in the information science era: Bibliometric analysis for the time frame from 2000-2023 - Khan, Muskan; Kumari, Arpana; Aggarwal, Prachi; Bhati, Babita (EAI Endorsed Transactions on Scalable Information Systems, 2024)
INTRODUCTION: To navigate the field of knowledge management (KM) for effective performance in data science, business intelligence, and database systems, all stakeholders, including academicians and professionals, must be informed of the recent state of practice and theory in KM. A detailed bibliometric study of publications can help with this problem by giving a comprehensive picture of the publications' trends and progression. From 2000 to 2023OBJECTIVES: To examine the pattern of publication in the area of knowledge management.METHODS: Two methodologies are employed to examine and interpret the bibliometric data acquired from the Scopus database. Citation and publication building evaluations were performed to gauge the emergence of the field of knowledge management, and secondly, VOS viewer software was used to simulate the projection of knowledge management grounded on bibliographic coupling (BC), co-citation, and co-occurrence (CC).RESULTS: The citation and publication structures indicate a steady improvement in the findings..
Keywords: Knowledge management; knowledge sharing; bibliometric analysis; information management